(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This study examines the abdominal compartment syndrome (ACS) in patients with urgent surgical pathologies in the context of military medicine. ACS is a critical condition associated with dysfunction of vital organs, complicating the course of the disease. The research focuses on the specific challenges of diagnosing, monitoring, and treating ACS under military conditions, including limited resources and the need for rapid evacuation. Clinical data were analyzed to identify key risk factors and develop recommendations for optimizing treatment strategies. The findings aim to improve the quality of medical care and reduce mortality in this patient group.